Mathematics learning support centres in Germany—an overview. (30th July 2020) - Schürmann, Mirko; Gildehaus, Lara; Liebendörfer, Michael; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard; Kuklinski, Christiane; Lankeit, Elisa
Abstract: Mathematics learning support centres (MLSC) are widely established and evaluated in English-speaking countries (such as the UK, Ireland and Australia). In most of these countries, several national surveys on MLSCs exist. They give an overview of the number of MLSCs as well as their characteristics in these countries. In Germany, there is a lack of studies on MLSCs and the landscape of MLSCs has not been described yet. This article presents basic information concerning counts of MLSCs and their characteristics at universities. Based on a three-step approach of analysing university homepages and additional personal contact via email or phone calls, we gathered typical MLSC features (e.g. staff quantities and qualification, opening and support hours, supported study programmes). We analysed 190 universities from a web-based register on study programmes. In total, we found 61 MLSCs located at 51 German universities. Another 16 support centres were specialized on mathematics didactics, which means they focussed on didactical and methodological support for preservice teacher students and often provided different teaching materials. Thirty-eight centres were located at universities (62.3%) and 23 MLSCs at universities of applied sciences and comparable universities (37.7%). The MLSCs were different in their sizes of staff and opening hours, and both the numbers of staff and the service hours differed greatly. The student groups MLSCs at German universities focus on differ concerning characteristics like study programme or semester. We will provide the main categories describing these groups. We seek to answer research questions concerning the characteristics of MLSCs in Germany and discuss the results compared to international findings. This information is useful for further international collaborative research, for example a standardized international survey. From a national perspective, these findings support networking and collaborations between the MLSCs as well. As some German MLSCs are facing financial cuts, these results might help in gaining additional funding.